Fabrication of SiOx-G/PAA-PANi/Graphene Composite With Special Cross-Doped Conductive Hydrogels as Anode Materials for Lithium Ion Batteries - Liao, Yuanhong; Liang, Kang; Ren, Yurong; Huang, Xiaobing (Frontiers in Chemistry, 2020)
Silicon oxides (SiOx) have been considered to be the likeliest material to substitute graphite anode for lithium-ion batteries (LIBs) due to its high theoretical capacity, appropriate working potential plus rich abundance. Nevertheless, the two inherent disadvantages of volume expansion and low electrical conductivity of SiOx have been a main obstacle to its application. Here, SiOx-G/PAA-PANi/graphene composite has been successfully synthesized by in-situ polymerization, in which SiOx-G particles linked together by a graphene-doped polyacrylic acid-polyaniline conductive flexible hydrogel and SiOx-G is encapsulated inside the conductive hydrogel. We demonstrate that SiOx-G/PAA-PANi/graphene composite possesses a discharge-specific capacity of 842.3 mA h g−1 at a current density of 500 mA g−1 after a cycle life of 100 cycles, and a good initial coulombic efficiency (ICE) of 74.77%. The superior performance probably due to the lithium ion transmission rate and the electric conductivity enhanced by the three-dimensional (3D) structured conductive polymer hydrogel.